2012
DOI: 10.1016/j.clnu.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Leucine supplementation chronically improves muscle protein synthesis in older adults consuming the RDA for protein

Abstract: SUMMARY Background & aim Protein-energy supplementation is routinely employed to combat muscle loss. However, success is often compromised by increased satiety, poor palatability, high costs and low compliance. Methods For 2-weeks we supplemented meals of older individuals with leucine (4 g/meal; 3 meals/day; days 2–14). Metabolic studies were performed prior to (Day 1) and following (Day 15) supplementation. Leucine was not provided on metabolic study days. Venous blood and vastus lateralis muscle biopsies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(114 citation statements)
references
References 30 publications
(42 reference statements)
2
109
0
3
Order By: Relevance
“…Since the liver does not possess any aminotransferase enzyme for metabolizing BCAA, these AA reach the blood and then skeletal muscles almost with the same concentrations that they appeared in the diet [41]. Thus, supplementation with BCAA, especially leucine, can potentially be of great importance to skeletal MPS [42,43]. Leucine is capable of inducing protein synthesis via the activation of mammalian target of rapamycin (mTOR) complex-1 signalling pathway, which plays a central role in cell growth, cellsurvival and protein synthesis.…”
Section: Protein and Amino Acidsmentioning
confidence: 98%
“…Since the liver does not possess any aminotransferase enzyme for metabolizing BCAA, these AA reach the blood and then skeletal muscles almost with the same concentrations that they appeared in the diet [41]. Thus, supplementation with BCAA, especially leucine, can potentially be of great importance to skeletal MPS [42,43]. Leucine is capable of inducing protein synthesis via the activation of mammalian target of rapamycin (mTOR) complex-1 signalling pathway, which plays a central role in cell growth, cellsurvival and protein synthesis.…”
Section: Protein and Amino Acidsmentioning
confidence: 98%
“…Of the few studies of amino acid or protein supplementation only, in interventions with essential amino acids, two studies found increases in lean body mass over the intervention period (142)(143)(144)149,150) . Generally, the response to protein and amino acid supplementation (with or without exercise interventions) has not been consistent and this may be due to differences in nutritional status at baseline, differing methods of measuring outcomes and geographical and racial differences (144,151) . Supplementation studies with protein have not always enhanced the effects of resistance training (152,153) .…”
Section: Interventions With Protein and Amino Acidsmentioning
confidence: 99%
“…The co-ingestion of leucine (10 g/L) and whey protein (60 g/L) following an acute bout of lower body resistance exercise (6 sets of 10 repetition for leg press and leg extension) in eight older men (75 ± 1 years) significantly increased the rates of muscle protein synthesis and whole-body protein balance [40]. Furthermore, Casperson et al [41] showed that 2 weeks of leucine supplementation (12 g/day) elevated the muscle protein synthetic response (i.e., augmented mTOR/p70S6K signaling) compared to a standardized meal in older adults without having any effect on lean tissue accretion. It is important to note that acute studies examining phosphorylation or insulin availability after resistance exercise and/or amino acid ingestion are primarily used to predict longer-term training outcomes (i.e., skeletal muscle hypertrophy) and as such, there may be a disconnect between these anabolic signals and end-point measures of protein synthesis [42].…”
Section: Branched Chain Amino Acidsmentioning
confidence: 99%